Analysis of Posyandu Status and Ownership of Health Service Facilities in the Area of Surakarta City Health Office: A Case Study of 2017-2021: Analisis Status Posyandu dan Kepemilikan Fasilitas Pelayanan Kesehatan di Wilayah Dinas Kesehatan Kota Surakarta: Studi Kasus Tahun 2017-2021 - Adilah, Farah; Setiyadi, Noor Alis (Prosiding University Research Colloquium, 2024)
Background: Based on data from the Ministry of Home Affairs in 2022, the number of Posyandu has increased every year, but there are still many inactive Posyandu and reduced ownership of health services. Little information describes the status of Posyandu in each sub-district in a city and the ownership of health services in the health department of a city in the period 2017-2021. Objective: This study aims to analyze the status of Posyandu and describe the ownership of health services in the Surakarta City Health Office area in the 2017-2021 period. Methods: This study is a descriptive study based on data reports of active Posyandu and health service ownership facilities in the Surakarta City Health Office area in 2017-2021 reported by 17 Puskesmas from 5 Districts. The data used in this study are secondary data. The data obtained were then analyzed descriptively using graphs and tables. Results: Surakarta City has 5 sub-districts with 17 health center coverage areas. Sociodemographic data explains that the population density of Surakarta city in 2018 was 11,762 people, when compared to 2017, namely 11,722 people, there was an increase in population. The number of active Posyandu status in the Surakarta city health service area in 2017-2021 which has increased is in Banjarsari sub-district. The number of Health Service Ownership in Surakarta City in 2017-2021 which increased was owned by the Ministry of Health consisting of hospitals and other service facilities, the Provincial Government consisting of hospitals and other service facilities, and BUMN consisting of other service facilities and pharmaceutical production and distribution facilities. Conclusion: The increasing population in Surakarta city in the period 2017-2021 affects the increasing number of Posyandu and health services.